ANALISIS KETERAMPILAN BERBICARA SISWA PADA TEMA 6 ENERGI DAN PERUBAHANNYA SUBTEMA 1 SUMBER ENERGI KELAS 3 SD NEGERI 2 BANGOAN - Margareta, Nancy (Universitas Negeri Padang, 2022)
The speaking skills intended in this study are the skills to express the articulation sounds or language sounds to express, express, or convey one's ideas, thoughts and feelings to be understood by others. The purpose of this study is to describe the data on how the analysis of students' speaking skills on the theme of energy 6 and the changes in sub-theme 1 energy source class III SD Negeri 2 Bangoan. The research approach used is a qualitative approach and the type of research used is descriptive. Related to data collection methods using interviews, tests and documentation. Interview and test methods are used to obtain information about students' speaking skills. Data analysis uses data reduction, data presentation, and drawing conclusions. The results of this study revealed that the sample taken by the researcher was one male student and one female student said male students were more skilled at speaking than female students